Development of modern logistics in Uzbekistan and its ways of improvement - Ibragimovna, Azizova Manzura; Erkinovna, Ishanxoddaeva Dilfuza (International Journal of Psychosocial Rehabilitation, 2020)
The following article analyzes the current conditions of logistics, the issues of properly assessing the opportunities created in our country, creating a wide range of opportunities for the development of logistics sector, as well as a thorough study and application of scientific and practical experience of developed countries in further improvement of the company's performance, as well as improvement of innovative structural changes in this sphere.